Role of γ-h2ax in dna-damage response and its possible clinical applications - Novotná, Eva; Tichý, Aleš; Foltánová, Karolína; Vávrová, Jiřina (Vojenské zdravotnické listy, 2011)
The integrity of the human genome is constantly threatened by exogenous or endogenous genotoxic agents that cause DNA damage. The ionizing radiation (IR)-induced DNA double-strand breaks (DSBs) are considered as the most deleterious forms of DNA damage which could lead to genomic instability and to cancer development, if left unrepaired. The DNA damage response (DDR) is comprised of a network of proteins that cooperate to regulate cell cycle progression and repair of DNA lesions. Our understanding of molecular basis of repair processes and of functions of repair proteins, as well as understanding of chromatin modifications may provide new possibilities in improvement of cancer management. Phosphorylation of histone variant H2AX at serine 139 (γ-H2AX) and formation of γ-H2AX repair foci seems to be the most sensitive DNA damage marker in the chromatin flanking the free DNA double-stranded ends in DSBs. Monitoring of γ-H2AX levels can serve for early indication of cancer development, as biomarker of cancer therapy efficiency or as a biodosimetric marker of radiation exposure.
Keywords: DNA vazebné proteiny; financování organizované; oprava DNA; Nuclear Proteins; Radiation, Ionizing; biologické markery; jaderné proteiny; Biomarkers; Phosphoserine; Neoplasms; Chromatin; nádory; vazba proteinů; Tyrosine; DNA; lidé; DNA Repair; ionizující záření; DNA Breaks, Double-Stranded; Financing, Organized; fosforylace; chromatin; dvouřetězcové zlomy DNA; DNA-Binding Proteins; tyrosin; histony; Histones; fosfoserin; Protein Binding; Phosphorylation; Humans